2020
DOI: 10.1109/access.2020.3022408
|View full text |Cite
|
Sign up to set email alerts
|

Optimal CTU-Level Rate Control Model for HEVC Based on Deep Convolutional Features

Abstract: This paper proposes an optimal rate control model based on deep neural network (DNN) features to improve the coding tree unit (CTU)-level rate control in high-efficiency video coding for conversational videos. The proposed algorithm extracts high-level features from the original and previously reconstructed CTU blocks based on a predefined DNN model of the visual geometry group (VGG-16) network. Then, the correlation of the high-level feature and quantization parameter (QP) values of previously coded CTUs is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The original studies [2,3] claimed that these values were provided based on video content. However, studies have discovered [30][31][32] that the existing R-λ model in the HM software is not optimal for the coding structure for the RA configuration.…”
Section: Current State Of the R−𝛌 Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The original studies [2,3] claimed that these values were provided based on video content. However, studies have discovered [30][31][32] that the existing R-λ model in the HM software is not optimal for the coding structure for the RA configuration.…”
Section: Current State Of the R−𝛌 Modelmentioning
confidence: 99%
“…This work determines the values of α and β for the framelevel rate control by considering the high-level features of a particular convolutional layer of the VGG-16 architecture. From previous work in [30], it is observed that a strong interrelationship between α-λ and β-λ is vital for improving the quality of the bpp-λ relationship. Consequently, it will also result in increasing the reconstructed video quality subjectively.…”
Section: Proposed Rate Control For the Ra Configuration In The Hevc Encodermentioning
confidence: 99%
“…Whereas the positive value indicates that the bit rate is amplified for thealike PSNR value. CTU rate control [12] estimates the allocation of bits to each CTU by exploiting the correlation between quantization parameters and features. Deep neural network based model improves the efficiency of CTU level rate control video coding.…”
Section: Figure 1 Video Compression Systemmentioning
confidence: 99%